2011
DOI: 10.1017/s0031182011000904
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and co-infection of Toxoplasma gondii and Neospora caninum in Apodemus sylvaticus in an area relatively free of cats

Abstract: The protozoan parasite Toxoplasma gondii is prevalent worldwide and can infect a remarkably wide range of hosts despite felids being the only definitive host. As cats play a major role in transmission to secondary mammalian hosts, the interaction between cats and these hosts should be a major factor determining final prevalence in the secondary host. This study investigates the prevalence of T. gondii in a natural population of Apodemus sylvaticus collected from an area with low cat density (<2·5 cats/km2). A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
50
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(52 citation statements)
references
References 43 publications
1
50
1
Order By: Relevance
“…Using the same detection approach, a comparably high prevalence of 40.8% was reported for A . sylvaticus in an area with low cat density suggesting that the contribution of vertical transmission to the epidemiological status of a rodent population may not be negligible [49]. …”
Section: Discussionmentioning
confidence: 99%
“…Using the same detection approach, a comparably high prevalence of 40.8% was reported for A . sylvaticus in an area with low cat density suggesting that the contribution of vertical transmission to the epidemiological status of a rodent population may not be negligible [49]. …”
Section: Discussionmentioning
confidence: 99%
“…T. gondii oocysts can be mechanically transmitted by certain types of insects to insectivorous bats (16,17). Recent studies have shown that congenital transmission may play an important role in sustaining T. gondii infection in some species, including sheep and small mammals (18,19). This transmission mode may be the main infection route in bat species, which needs further investigation.…”
Section: Genotyping Of T Gondii In Batsmentioning
confidence: 99%
“…[16][17][18] However, the frequency of this mode of transmission in natural populations of animals, or humans, is less clear. PCR based studies on the transmission of T. gondii in several mammalian species, e.g., mice, woodmice 17,[19][20][21] and sheep [22][23][24][25] have suggested that congenital transmission may be occurring at a higher frequency than previously thought. Although higher frequencies of congenital transmission are reported in these studies, in many cases there seems to be no measurable disease effect on the neonates in these species.…”
Section: Introductionmentioning
confidence: 96%